Flanking the major Plum pox virus resistance locus in apricot with co-dominant markers (SSRs) derived from candidate resistance genes - Sicard, O.; Marandel, G.; Soriano, J. M.; Lalli, D. A.; Lambert, P.; Salava, J.; Badenes, María L.; Abbott, Albert Glenn; Decroocq, V. (2017)
Plum pox virus (PPV) is a potyvirus that causes sharka disease in infested stone fruit trees (Prunus species, peach, apricot, plum). In apricots, the resistance is controlled by a major quantitative trait locus that explains up to 70% of the phenotypic variance; it is localised in the upper part of linkage group 1. In this report, we transformed candidate genes that mapped in the region of the apricot resistance locus into polymerase chain reaction markers (SSCP and SSR) and tested for their co-localisation with the major PPV resistance locus in related and unrelated populations. Three populations of F1 and F2 individuals issued from crosses between the PPV-resistant cultivar ‘Stark Early Orange’ or ‘Goldrich’ and three susceptible parents were used in this study. Molecular-marker data were collected to determine the linkage relationship between the PPV resistance locus in apricots and markers that target candidate disease-resistance genes. In addition, SSR markers linked to resistance-gene candidates were mapped to positions flanking the PPV resistance locus in different apricot populations. Therefore, we demonstrate that this strategy helps to saturate the major genomic region controlling resistance to PPV in apricot with valuable co-dominant markers